Radiometals: towards a new success story in nuclear imaging?. Issue 11 (1st December 2014) - Brasse, David; Nonat, Aline
Abstract : The use of radiometal isotopes in positron emission tomography: a new success story in nuclear imaging? Abstract : Several limitations of 18 F and other non-metallic isotopes have been emphasized by the development of macromolecular biotargeting agents for cancer, including peptides, antibodies, fragments and oligonucleotides, which typically have biological half-lives that are much longer than the radioactive half-life of 18 F. Based on the 18 F-FDG success story, we can wonder whether all critical criteria are or can be fulfilled for the radiometallated bioconjugates to start out from the crowd and which metals have the best chance of success. In this paper we give a brief overview of radiometal isotopes having the potential for PET imaging in terms of physical properties, production capacity and associated chemistry.